Effect of Homeopathic Medicine (Alfalfa), Methionine and Lysine Supplementation in Low Protein Based Diets on the Performance of Broiler Chicken - Rawat, D.; Shah, R.; Nepali, D.B.; Yadav, J.L. (International Journal of Applied Sciences and Biotechnology, 2018)
An experiment was conducted, with objective to determine the feed consumption, final live weight, weight gain, feed efficiency and economy in broiler chicken fed with locally available low protein based diets (20 percent CP in starter and 18 percent CP in finisher) supplemented with methionine, lysine and homeopathic medicine alfalfa. For this hundred fifty day-old birds of commercial broiler (Vencobb) were randomly assigned to five dietary treatments(10 chicks/treatment) and replicated three times in CRD with treatments composition of low protein based diets (LPB) (T0), LPB+ 100g/100 met + 300g/100 lysine (T1), LPB + 200g/100 met +300g/100lysine (T2), LPB + Alfalfa 5ml/100 chicks 2 day in week with drinking water (T3) and LPB + Alfalfa 5ml/100 chicks 3 day in week with drinking water (T4). Synthetic methionine and lysine was used for supplementation of deficient amino acid. Same condition was applied in finisher diets of broiler chicken. The result showed that chicks fed with LPB in both starter and finisher diet had significantly (P<0.05) lower feed intake, final live weight , total weight gain, feed efficiency and income over feed and chicks cost (IOFCC) with compromising chicks fed with LPB with addition of methionine and lysine each and also homeopathic medicine alfalfa in starter and finisher period. Highest feed intake, final live weight, weight gain, feed efficiency was obtained with treatment (T1) followed by treatment (T2). However, positive growth response and better health status of chicks was also observed from supplementation of homeopathic medicine alfalfa with LPB and non-significant difference on Income Over Feed and Chicks Cost was obtained with treatment (T1). So, it was concluded that with supplemental methionine, lysine and alfalfa, the CP level of broiler chicks could be reduced up to 20 percent in starter and 18 percent in finisher diets without adverse effect on feed intake, final live weight, weight gain, feed efficiency and Income overfeed and chicks cost, provided under locally based feed ingredients. Int. J. Appl. Sci. Biotechnol. Vol 6(2): 174-180